New Method for the Hydro-insulating of Construction Concrete by the Use of a Multifunctional Textile Geo-composite - Szafran, Krzysztof; Wojtysiak, Jan; Szer, Jacek (Instytut Biopolimerów i Włókien Chemicznych (IBWCh) , Łódź, Polska, 2014)
A new method is presented to provide damp-proof insulation in horizontal outer constructions such as balconies, terraces and loggias, both in new buildings and existing structures requiring renovation. A newly prepared textile geo-composite is proposed for this purpose. Presented are results of experimental examination of the geo-composite prepared, made on a laboratory-and semi-technical scale to identify its physical properties in relation to the curing of concrete during maturation, and to the damp-proof function in exploitation expected.
Keywords: multifunctional textile geo-composite; hydro-insulation; concrete curing; dampproof care; drainage nonwoven